Homogeneous silver colloidal substrates optimal for metal-enhanced fluorescence. Issue 22 (22nd March 2019) - Lee, Daedu; Lee, Jaebeom; Song, Junghyun; Jen, Myungsam; Pang, Yoonsoo
Abstract : Particle-size-dependent fluorescence enhancements and dynamics on homogeneous silver nanosurfaces show a strong dependence on the spectral properties of surface plasmons. Abstract : Homogeneous silver colloidal films (SCFs), composed of silver nanoparticles 67–193 nm in diameter, were synthesized by a seeded-growth method as the substrates for metal-enhanced fluorescence (MEF). The homogeneity and uniform particle distribution of the SCFs showed many advantages for the exploration of the MEF mechanism. The fluorescence enhancement of 4-(dicyanomethylene)-2-methyl-6-(4-dimethylaminostyryl)-4 H -pyran (DCM) and rhodamine 700 (Rh700) dyes dispersed in a thin layer of polystyrene (PS) with the SCFs was observed by time-resolved fluorescence spectroscopy. The fluorescence enhancements of DCM and Rh700 become larger when the surface plasmon resonance bands of SCFs overlap the emission bands of dyes. The particle-size-dependent changes of the radiative and non-radiative rate constants of both dyes with the SCFs are estimated by an improved analysis combining the fluorescence intensity and lifetime measurements and the finite-difference time-domain method simulations.